2015
DOI: 10.2495/esus150171
|View full text |Cite
|
Sign up to set email alerts
|

Performance of a solar PV tracking system on tropic regions

Abstract: Climate change is currently a large concern for human society, particularly our high dependence on fossil fuels. A considerable amount of research effort is focused on renewable energies, especially solar photovoltaic (PV) generation systems. For solar PV systems, energy conversion efficiency is an active research topic, with many approaches being developed to solve this problem. One of these approaches is solar tracking systems, where the solar PV moves with the sun in order to capture the maximum direct sola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 14 publications
0
1
0
1
Order By: Relevance
“…Diversos estudos foram conduzidos visando avaliar o aumento de eficiência de um sistema com rastreamento solar, de um e dois eixos, comparando-os a sistemas estáticos, bem como os impactos térmicos que afetam a eficiência de sistemas fotovoltaicos. Esses estudos foram realizados em diversas latitudes e longitudes, bem como utilizando intervalos de tempo variados, considerando um único ciclo diário, poucos dias ou alguns meses (Bittencourt et al, 2017;Fernandes, 2014;Oliveira, 2007;Berwanger, 2019;Carvalho, 2011;Frosi et al, 2018;Meceneiro, 2018;Hoffmann et al, 2018;Bona et al, 2015;Passos et al, 2017;Martins, 2016;Lopes, 2016;Konneh et al, 2021;Assaf, 2014;Lo et al, 2015;Garcia et al,2015). Contudo, a presente pesquisa norteou-se na metodologia científica desenvolvida por Severino (2018).…”
Section: Metodologiaunclassified
“…Diversos estudos foram conduzidos visando avaliar o aumento de eficiência de um sistema com rastreamento solar, de um e dois eixos, comparando-os a sistemas estáticos, bem como os impactos térmicos que afetam a eficiência de sistemas fotovoltaicos. Esses estudos foram realizados em diversas latitudes e longitudes, bem como utilizando intervalos de tempo variados, considerando um único ciclo diário, poucos dias ou alguns meses (Bittencourt et al, 2017;Fernandes, 2014;Oliveira, 2007;Berwanger, 2019;Carvalho, 2011;Frosi et al, 2018;Meceneiro, 2018;Hoffmann et al, 2018;Bona et al, 2015;Passos et al, 2017;Martins, 2016;Lopes, 2016;Konneh et al, 2021;Assaf, 2014;Lo et al, 2015;Garcia et al,2015). Contudo, a presente pesquisa norteou-se na metodologia científica desenvolvida por Severino (2018).…”
Section: Metodologiaunclassified
“…The study conducted in 2015 showed that a single axis solar tracking system, when used in the tropical area, resulted in a more extensive power conversion of about 25 % compared to fixed panels [9]. Research in 2012 in Malaysia, the performance ratio of P-Si type photovoltaics of 59.40 %, uses a solar tracker system with one axis [10]. Therefore, it is necessary to compare the performance between two methods of tracking the sun that is with one axis and two-axis using ANFIS (Adaptive Neuro-Fuzzy Inference System) control in the tropical area, so it can show the difference in performance produced by the solar tracker system with one axis and two-axis solar tracking.…”
Section: Introductionmentioning
confidence: 99%